2014
DOI: 10.1371/journal.pone.0113917
|View full text |Cite
|
Sign up to set email alerts
|

A Fully Automated Microfluidic Femtosecond Laser Axotomy Platform for Nerve Regeneration Studies in C. elegans

Abstract: Femtosecond laser nanosurgery has been widely accepted as an axonal injury model, enabling nerve regeneration studies in the small model organism, Caenorhabditis elegans. To overcome the time limitations of manual worm handling techniques, automation and new immobilization technologies must be adopted to improve throughput in these studies. While new microfluidic immobilization techniques have been developed that promise to reduce the time required for axotomies, there is a need for automated procedures to min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 37 publications
0
48
0
Order By: Relevance
“…Significant effort has been put into developing microfluidic methods for worm handling, facilitating larger scale approaches (Guo et al 2008). A fully automated platform for laser axotomy has been reported (Gokce et al 2014), and it will be interesting to see the results from these approaches.…”
Section: Regeneration Screens: Methods and Metricsmentioning
confidence: 99%
“…Significant effort has been put into developing microfluidic methods for worm handling, facilitating larger scale approaches (Guo et al 2008). A fully automated platform for laser axotomy has been reported (Gokce et al 2014), and it will be interesting to see the results from these approaches.…”
Section: Regeneration Screens: Methods and Metricsmentioning
confidence: 99%
“…Thus, with this mutant, very large numbers of axons can be injured (at the expense of temporal and spatial precision), facilitating genetic and genomic screening (Hammarlund et al, 2009; Rohde et al, 2009; Nix et al, 2014). An alternative approach is to automate laser surgery, potentially increasing the number of axons that can be injured and analyzed (Guo et al, 2008; Gokce et al, 2014). The availability of diverse axon injury models in C. elegans enables researchers to select the optimal approach for a given experiment.…”
Section: Techniques For Axon Injury: Lasers and Geneticsmentioning
confidence: 99%
“…8,9,[12][13][14][15][16][17] Moreover, microfluidic devices can be automated to handle single or a population of C. elegans in a high-throughput fashion, which enables large-scale assays such as drug and genetic screens. [15][16][17][18][19][20][21][22] In previous work from our group, we designed a simple microfluidic device to examine the swimming behaviors of C. elegans under electric fields, termed electrotaxis, and demonstrated that changes in movement are reliable indicators of neurodegeneration and harmful effects of toxic chemicals on C. elegans health. [23][24][25] However, the inherent manual operation of the devices makes the screening process labor intensive and time consuming, which limits largely the practical application of the method.…”
Section: Introductionmentioning
confidence: 99%